A case series of urinary bladder rhabdomyosarcoma in seven dogs - Alessio Pierini; Maria Carla Criscuolo; Roberta Caccamo; Enrico Bottero; Andrea Campanile; Guido Pisani; Veronica Marchetti; Elena Benvenuti (Open Veterinary Journal, 2023)
Background: Juvenile urinary bladder rhabdomyosarcoma is a known entity, however literature regarding its clinical behavior and endoscopic features is scarce. The aim of this study was to describe clinical, endoscopic features and outcome of urinary bladder rhabdomyosarcoma in dogs. Case Description: Dogs undergoing transurethral endoscopy and with a histological diagnosis of urinary bladder rhabdomyosarcoma were retrospectively collected. Seven dogs with a median age of 18 months (range 6-32 months) were included in this retrospective, multicenter, descriptive study. Median tumor size was 58 mm (range 30-65 mm), and tumor location was bladder neck in three cases, trigone in two cases and bladder body in two cases. Two dogs had monolateral ureteral obstruction. Two dogs presented with regional lymphadenopathy and one dog had lung lesions suggestive of metastatic disease. A grape-like mass was reported in four cases and solid in two, with variable consistency (two friables, two firms, two not reported). Tumor treatments included surgery in three cases, surgery and adjuvant doxorubicin in one case, and palliative therapy in three cases. Overall median survival time was 45 days. Survival times were shorter (range 20-45 days) for dogs treated with palliative care than for dogs treated with curative-intent treatment (range 70-120 days). Conclusion: Urinary bladder rhabdomyosarcoma should be considered as a differential diagnosis in young dogs presenting with bladder masses. In this study, urinary bladder rhabdomyosarcoma confirmed its aggressive clinical behavior. Surgery and chemotherapy seem to increase survival times but prognosis remains poor. [Open Vet J 2023; 13(11.000): 1498-1503]